If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3.4x) + 7 = x + 54.6 Reorder the terms: 7 + (3.4x) = x + 54.6 Reorder the terms: 7 + (3.4x) = 54.6 + x Solving 7 + (3.4x) = 54.6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + (3.4x) + -1x = 54.6 + x + -1x Combine like terms: (3.4x) + -1x = 2.4x 7 + 2.4x = 54.6 + x + -1x Combine like terms: x + -1x = 0 7 + 2.4x = 54.6 + 0 7 + 2.4x = 54.6 Add '-7' to each side of the equation. 7 + -7 + 2.4x = 54.6 + -7 Combine like terms: 7 + -7 = 0 0 + 2.4x = 54.6 + -7 2.4x = 54.6 + -7 Combine like terms: 54.6 + -7 = 47.6 2.4x = 47.6 Divide each side by '2.4'. x = 19.83333333 Simplifying x = 19.83333333
| 2x+4x-9+x^2+2x+9=180 | | 0=x^2+13x+30 | | 13n=.26 | | 3x-1=0.50(4x+6) | | 6x^2+36+48=0 | | -7x-8=4x+6 | | 4/13p=-16/5 | | -8/3÷3 | | -18=0(-3)+b | | -5/6(6)=x | | -17=0(-2)+b | | -21x+7=14 | | 550-30y/50 | | -5/6y=1 | | M=-0.711A+206.6 | | 1.50b=31.50 | | 2x^2=-21x | | -3.5x=9.2 | | 5/6x72/5 | | 17=0(-2)+b | | -5/6y=0 | | 21x(2/7)=6 | | -4.3x=-8.6 | | F(x)=x^4-4x^3-9x^2+36 | | 0.2x-0.5x-3=18 | | -3x-14=y | | y^2+54=0 | | 17+33x=5 | | -3x+7(2)=-16 | | -x=59 | | 5t-9t+1t=0 | | -6=5r |